Typical earthquake disasters in Guizhou during 2010 to 2022 and their implications - Yafang Shi; Peng Qiu; Delong Tang; Xiang Fang; Danqin Luo; Peng Li (地震科学进展)
From 2010 to 2022, seven earthquakes with a magnitude of around 4.0 occurred in Guizhou Province, causing damage to housing facilities, casualties, property, and other secondary disasters. To analyze the characteristics of geological disasters and building damage in these earthquakes, a seismic damage investigation was conducted in the earthquake area, to analyze the characteristics and causes of geological disasters and building damage such as landslides and collapses. Investigation and analysis showed that frequent earthquake disasters in Guizhou mainly include damage to buildings and other structures caused by earthquakes, landslides and collapses induced by earthquakes leading to casualties, road damage, and increased risk of geological hazards. In various types of housing construction, brick and wood structure houses had slight cracking and damage, and the roof tiles of old houses had fallen off. Non-structural components such as doors, windows, and ceilings in concrete structure buildings were damaged. Wooden houses almost had no damage. Based on these, opinions and suggestions are proposed for the prevention and control of earthquake geological disasters, seismic fortification of buildings, and earthquake emergency response in Guizhou, with the aim to continuously enhancing Guizhou people’s awareness of earthquake prevention and disaster reduction, improving their ability to prevent and control earthquake risks.